The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/itor.12577
|View full text |Cite
|
Sign up to set email alerts
|

A survey on obstacles and difficulties of practical implementation of horizontal collaboration in logistics

Abstract: During recent years, horizontal collaboration in logistics has gained attention because of achieved potential benefits such as cost reduction, an increase in fulfillment rates, and a decrease in CO2 emissions owing to reductions in traveled distances. Successful real‐world cases, however, are rare since horizontal cooperation in logistics is not usually sustainable. This paper pays attention to this paradox of the lack of cases and discusses 16 identified practical issues that could explain this phenomenon. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 82 publications
(161 reference statements)
3
83
0
1
Order By: Relevance
“…The result shows that the two main factors that affect the participation decision for collaboration are the expected benefit (positive effect from joining in collaboration) and the competitive intelligence risks (the problem of sharing information, possibly resulting in a loss of competitive advantage). Basso, D'Amours [54] found that the cost allocation for collaboration is the most studied practical issue. Furthermore, the study result indicates that trust and the coordination mechanism are significant variables for the implementation of logistics collaboration.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…The result shows that the two main factors that affect the participation decision for collaboration are the expected benefit (positive effect from joining in collaboration) and the competitive intelligence risks (the problem of sharing information, possibly resulting in a loss of competitive advantage). Basso, D'Amours [54] found that the cost allocation for collaboration is the most studied practical issue. Furthermore, the study result indicates that trust and the coordination mechanism are significant variables for the implementation of logistics collaboration.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…In recent years, the concept of collaboration has received increasing attention in production (e.g., Leng and Jiang 2018;Salamati-Hormozi et al 2018), logistics (e.g., Basso et al 2019;Guajardo et al 2018), and supply chain management (e.g., Herczeg et al 2018;Ponte et al 2018). In this context, collaboration is typically seen as a form of cooperation between two or more independent companies planning and executing jointly specific operations.…”
Section: Review Of Relevant Researchmentioning
confidence: 99%
“…The aim is to achieve mutual benefits, which can be related to cost reductions or the compliance with environmental regulations, for instance. Most commonly, cooperation can either take place between (competing) companies on the same stage of a supply chain (horizontal collaboration) or among partners that operate on different supply chain levels (vertical collaboration) (Basso et al 2019;Simatupang and Sridharan 2002).…”
Section: Review Of Relevant Researchmentioning
confidence: 99%
“…is problem relates to the complete set partitioning problem [6] in the Operations Research and Management Science (OR/MS) literature and is commonly formulated as a coalition structure generation problem [2] in cooperative game theory. Although there is a vast body of game theory literature dealing with coalition structure generation problems issues, the OR/MS literature is more sparse in this stream [4,7,8].…”
Section: Introductionmentioning
confidence: 99%